Anne Shirley, Storyteller:: Orality and Anne of Green Gables - Frever, Trinna (Studies in Canadian Literature / Études en littérature canadienne, 2005)
L.M. Montgomery's use of orality within the print narrative of Anne of Green Gables, established through the presentation of Anne as storyteller, has both narratological and social implications. Anne's continual storytelling is woven together with the voice of the omniscient narrator as well as other members of the community, creating a polyvocal narrative style that collapses the author-narrator-reader hierarchy. Anne's characterization as tribal, or community, storyteller serves both intertextual and extratextual functions as she demonstrates how story has the capacity of healing communal rupture by encouraging imagination and personal agency. The fairy content of her stories also connects Anne and the novel itself to an older, oral tradition outside the world of Green Gables and, together with the use of invocation, generates an eternal temporality to the narrative. Montgomery's use of orality recuperates the reader into the communal experience of a listening audience that oral storytelling represents.